2020
DOI: 10.1002/smi.2953
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among adverse childhood experiences, posttraumatic stress disorder symptom clusters, and health in women veterans

Abstract: Adverse childhood experiences (ACEs) increase risk for negative health outcomes. The goal of this study was to examine the relationships among cumulative ACEs, ACEs type, posttraumatic stress disorder (PTSD) symptoms, PTSD symptom clusters, and physical health symptoms in a sample of women veterans (N = 76). Bivariate correlations were used to determine which ACE domains were associated with PTSD and physical health symptoms. Follow-up linear regressions indicated cumulative ACEs were significantly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…First, it could highlight a difference in the childhood environment of many individuals who volunteer to join the military. Previous research with volunteer-era veterans has found elevated risks of childhood adversity (Blosnich et al, 2014) and high ACE exposure in this population (Lamson et al, 2020;Wooldridge et al, 2020). Second, it could be related to differences in the way childhood physical abuse is defined and measured across studies.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…First, it could highlight a difference in the childhood environment of many individuals who volunteer to join the military. Previous research with volunteer-era veterans has found elevated risks of childhood adversity (Blosnich et al, 2014) and high ACE exposure in this population (Lamson et al, 2020;Wooldridge et al, 2020). Second, it could be related to differences in the way childhood physical abuse is defined and measured across studies.…”
Section: Discussionmentioning
confidence: 87%
“…A recent systematic review concluded that MST survivors are at increased risk for further victimization after military service (Tirone et al, 2020). In the study by Wooldridge et al (2020), 77% of the sample reported MST, and 44% of the sample reported experiencing postdeployment assault. Within and outside of the military, women have a higher risk of experiencing sexual victimization than their male counterparts (Russo & Pirlott, 2006;Schry et al, 2016).…”
Section: Victimization In Us Military Veteransmentioning
confidence: 95%
See 2 more Smart Citations
“…Increasing evidence suggests that anxiety/depression symptoms may mediate the relationship between ACEs and somatic symptoms (Bonvanie et al, 2017;Bugge et al, 2017;Hammond et al, 2019;Kugler et al, 2012;McCall-Hosenfeld et al, 2014;Wooldridge et al, 2020). For example, Kugler et al (2012) conducted a cross-sectional study on children (ages 8-17 years) residing in foster homes and have found that anxiety symptoms mediated the relationship between sexual abuse and somatic symptoms (Kugler et al, 2012).…”
Section: The Mediating Role Of Anxiety and Depression Between Aces An...mentioning
confidence: 99%